2019
DOI: 10.2147/cmar.s208708
|View full text |Cite
|
Sign up to set email alerts
|

<p>miR-625 reverses multidrug resistance in gastric cancer cells by directly targeting ALDH1A1</p>

et al.

Abstract: Background: microRNAs (miRNAs) are emerging as critical regulators of multidrug resistance (MDR) in gastric cancer, a major cause of chemotherapy failure. miR-625 is downregulated in gastric cancer and negatively associated with metastasis. In the current study, we aimed to investigate whether miR-625 regulates MDR in gastric cancer. Methods: The level of miR-625 in gastric cancer cells with or without MDR was quantified by quantitative reverse transcription PCR (qRT-PCR) ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…HMGA2 involvement in EMT is very well documented in a variety of tumors, and we have discussed some of its involvement in tumor EMT and migration in connection with NCCs [146,147,[150][151][152][153][154][211][212][213][214][215][216][217][218][219]. HMGA2 is also involved in EMT of crystalline epithelial cells in lens fibrosis; this process apparently uses the same pathway of TGFβ-regulated EMT, recruiting SMAD3, HMGA2, and SNAI [220][221][222].…”
Section: Hmga In Emtmentioning
confidence: 98%
“…HMGA2 involvement in EMT is very well documented in a variety of tumors, and we have discussed some of its involvement in tumor EMT and migration in connection with NCCs [146,147,[150][151][152][153][154][211][212][213][214][215][216][217][218][219]. HMGA2 is also involved in EMT of crystalline epithelial cells in lens fibrosis; this process apparently uses the same pathway of TGFβ-regulated EMT, recruiting SMAD3, HMGA2, and SNAI [220][221][222].…”
Section: Hmga In Emtmentioning
confidence: 98%
“…Thus, miRNAs are thought to be markers of cancers diagnosis, progression, and prognosis . Many human miRNAs have been confirmed to be dysregulated in GC, including miR‐32‐5p, miR‐544a, miR‐1297, miR‐625, and miR‐383‐5p . Up to now, miR‐665 has been reported to function as an oncogene in breast cancer, hepatocellular carcinoma, acute lymphoblastic leukaemia, or function as a tumour suppressor in colorectal cancer, cervical cancer, and ovarian cancer; the functions of miR‐665 in GC were rare unexplored previously.…”
Section: Introductionmentioning
confidence: 99%
“…Noticeably, miRNAs are strongly implicated in the chemotherapy resistance of GC. For example, Gong et al (17) found that the expression of miR-625 was decreased in multidrug resistance compared to that of the chemosensitive counterparts, and overexpression of miR-625 significantly enhanced the sensitivity and induced cell apoptosis in GC. Li et al (18) demonstrated that miR-200c-3p upregulation reversed drug resistance of human GC via regulating NER-ERCC3/ 4 pathway.…”
Section: Introductionmentioning
confidence: 99%